Magnetic resonance measurement of total intracranial volume among malay population: accuracy of alternative measurement methods - Musa, Busro (2011)
Total intracranial volume (TIV) is defined as the volume within the cranium, including the brain, meninges and cerebrospinal fluid. It provides a stable and accurate normalization factor for estimating volumetric changes of brain structures in studies of ageing process, various neurological and neuropsychiatric diseases as it is constant and did not changed with increasing age and less vulnerable to pathological changes. With the advance of the technology, magnetic resonance (MR) imaging has made possible accurate measurements of the brain and its substructures. Various methods of MR volumetric measurement of TIV had been established and manual method is the best. The best manual MR volumetry is obtained by measuring each MR slices that cover the brain. However, obtaining TIV via the standard manual method is time consuming. Therefore alternative volumetric measurement methods which reduced the time consumption in measuring TIV without alteration of their accuracy and reliability should be established. This study had calculated the estimation of TIV using alternative measurement and standard methods. Thus, comparison of the accuracy of measuring TIV using alternative measurement methods with the standard measurement method can be evaluated.